2023
DOI: 10.1007/s00702-023-02597-7
|View full text |Cite
|
Sign up to set email alerts
|

Knock-out of the critical nitric oxide synthase regulator DDAH1 in mice impacts amphetamine sensitivity and dopamine metabolism

Abstract: The enzyme dimethylarginine dimethylaminohydrolase 1 (DDAH1) plays a pivotal role in the regulation of nitric oxide levels by degrading the main endogenous nitric oxide synthase inhibitor asymmetric dimethylarginine (ADMA). Growing evidence highlight the potential implication of DDAH/ADMA axis in the etiopathogenesis of several neuropsychiatric and neurological disorders, yet the underlying molecular mechanisms remain elusive. In this study, we sought to investigate the role of DDAH1 in behavioral endophenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 109 publications
0
0
0
Order By: Relevance
“…The DDAH-1 deletion in WT rats did not influence on locomotor activity and muscle strength, consistent with that in DDAH-1 KO mouse constructed by a fourth-exon deletion. These KO mice exhibited unaltered general locomotor activity while reduced sensitivity to amphetamine indicating impaired dopamine system [35]. In our study, DDAH-1 deletion exacerbated impaired locomotor function and dopaminergic neurodegeneration in PD rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The DDAH-1 deletion in WT rats did not influence on locomotor activity and muscle strength, consistent with that in DDAH-1 KO mouse constructed by a fourth-exon deletion. These KO mice exhibited unaltered general locomotor activity while reduced sensitivity to amphetamine indicating impaired dopamine system [35]. In our study, DDAH-1 deletion exacerbated impaired locomotor function and dopaminergic neurodegeneration in PD rats.…”
Section: Discussionsupporting
confidence: 51%
“…It did not additionally induce other cellular damages under a relatively modest concentration of ROT. Moreover, Kozlova et al suggested DDAH-1 influenced animal behavior and the dopamine system, most probably via the NO pathway [35]. However, the study lacked experimental evidence for the impact of DDAH-1 loss on the brain or specific region changes in NO levels.…”
Section: Discussionmentioning
confidence: 96%